Microvessel density and vascular endothelial growth factor expression as predictors of childrens' survival from cerebellar medulloblastoma - (:unkn) unknown (ELSEVIER SCI LTD, 2009)
Cerebellar medulloblastoma is the most common malignant brain tumor of childhood. This neoplasm is highly vascular and has a high growth rate. We aimed to determine whether high microvessel density (MVD) and expression of vascular endothelial growth factor (VEGF) in medulloblastoma tissue is correlated with survival time in children with this tumor. Tissue from 32 cerebellar medulloblastomas in 14 girls and 18 boys was studied. The standard-risk group comprised patients older than 3 years, without metastases of medulloblastoma and a residual post-operative tumor with a surface area less than 1.5 cm(2). The patients assigned to a high-risk group had at least one of the following indicators: younger than 3 years, metastases, or a residual post-operative tumor with a surface area larger than 1.5 cm(2). For each tumor, MVD was determined and the expression of VEGF was assessed using immunohistochemical techniques. The 5-year Survival rate for the 32 patients was 56.2%. Five-year survival rates were 70.6% and 40.0% for patients in the standard-risk and high-risk groups, respectively. The mean (+/- standard deviation, SD) MVD for all patients was 22.0 +/- 9.1 microvessels per 0.7 mm(2). There was no difference in the survival rate between the groups with above-average MVD and below-average MVD (66.7% and 50.0%, respectively). Testing revealed 7 tumors with VEGF expression and 25 without. The 5-year survival rates for these 2 groups were not significantly different (57.1% vs. 56.0%, respectively). The mean (+/- SD) MVD values for the VEGF-positive and VEGF-negative groups were not significantly different (19.1 +/- 6.5 vs. 22.9 +/- 9.7 microvessels per 0.7 mm(2), respectively, Mann-Whitney U-test = 78.5, Z = -0.41, p = 0.68). There were no significant correlations between risk groups and expression of VEGF or MVD. These results indicate that neither high MVD nor the expression of VEGF in tumor tissue predicts poor prognosis in children with cerebellar medulloblastoma. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Cerebellar medulloblastoma; Children; Microvessel density; Survival rate; Vascular endothelial growth factor; BRAIN-TUMORS; BREAST-CARCINOMA; ANGIOGENESIS; CHILDHOOD; GLIOMA; VEGF